"Frappés, friends, and fun": Affective labor and the cultural industry of girlhood. (August 2021) - Coulter, Natalie
In the cultural industries of girlhood, tween girls are almost always shown to be having fun. This article focuses mainly on tween retailer Justice, its corporate communications materials, the images in its online retail spaces, and the slogans on the T-shirts that the company sells. I argue that fun is a commercial epistemology that reaffirms the boundaries between the separate market segments of youth and legitimates market incursions into girlhood. As a result, fun becomes a political action that functions as a means to depoliticize girlhood. This article builds upon Sara Ahmed's work on the happy housewife as a fantasy figure that obscures the unequal divisions of labor in patriarchal capitalism in its assertion that the tween girl is a fantasy figure of the 21st century consumer culture whose fun is a form of commodified, depoliticized girl-power that reifies girls as productive economic subjects.